Comparative evaluation of the sealing ability of an alkasite restorative material and resin-modified glass ionomer cement in primary molars: An In vivo study - M P Pooja; Y M Karuna; Arathi Rao; Ethel Suman; Srikant Natarajan; B S Suprabha (Wolters Kluwer Medknow Publications, 2022)
Background: Cention N is relatively new and an "alkasite" restorative material, indicated for direct restorations. Aim: The aim of this study was to comparatively evaluate the sealing ability of Cention N and resin-modified glass ionomer cement (GIC) when used to restore primary molars. Methods and Materials: It is a split-mouth study. Twenty children having bilateral deep dentinal caries involving primary molars requiring restoration were selected. After caries excavation under the rubber dam, samples were collected from the cavity. Restorations of the teeth were done using either resin-modified GIC (RMGIC) or Cention N. Patients were recalled after 6 weeks and the restorations done previously were removed using contra angled micromotor handpiece under rubber dam isolation. The samples were collected again. The collected samples were used to estimate the total viable count. Statistical Analysis: The pretreatment, posttreatment colony counts, and the differences between the groups were analyzed using paired t-test. Results: No statistically significant difference was observed in the mean differences of the pre- and posttreatment colony count between alkasite restorative material and RMGIC (P = 0.056). Conclusion: Restorations done using alkasite restorative material and RMGIC performed equally in terms of sealing ability.